Does a meso‐caval shunt have positive effects in a pig large‐for‐size liver transplantation model?. (24th April 2017) - Tannuri, Ana Cristina Aoun; de Albuquerque Rangel Moreira, Daniel; Belon, Alessandro; Coelho, Maria Cecília Mendonça; Gonçalves, Josiane Oliveira; Serafini, Suellen; Tannuri, Uenis
Abstract: In pediatric liver transplantations with LFS grafts, higher incidences of graft dysfunction probably occur due to IRI. It was postulated that increasing the blood supply to the graft by means of a meso‐caval shunt could ameliorate the IRI. Eleven pigs underwent liver transplantation and were divided into two groups: LFS and LFS+SHUNT group. A series of flowmetric, metabolic, histologic, and molecular studies were performed. No significant metabolic differences were observed between the groups. One hour after reperfusion, portal flow was significantly lower in the recipients than in the donors, proving that the graft was maintained in low portal blood flow, although the shunt could promote a transient increase in the portal blood flow and a decrease in the arterial flow. Finally, it was verified that the shunt promoted a decrease in inflammation and steatosis scores and a decrease in the expression of the eNOS gene (responsible for the generation of nitric oxide in the vascular endothelium) and an increase in the expression of the proapoptotic gene BAX . The meso‐caval shunt was responsible for some positive effects, although other deleterious flowmetric and molecular alterations also occurred.